2015
DOI: 10.1016/j.ajo.2014.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Stereopsis Results at 4.5 Years of Age in the Infant Aphakia Treatment Study

Abstract: Purpose To determine whether stereopsis of infants treated for monocular cataracts varies with the type of optical correction used. Design Randomized prospective clinical trial Methods The Infant Aphakia Treatment Study randomized 114 patients with unilateral cataracts at age 1 to 7 months to either primary intraocular lens (IOL) or contact lens correction. At 4.5 years of age a masked examiner assessed stereopsis on these patients using three different tests: 1) Frisby; 2) Randot Preschool; and 3) Titmus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…[9][10][11] We have previously reported a positive stereopsis response to at least one stereopsis test at age 4.5 years in 25% of children in the IATS cohort. 12 We reported that positive stereopsis responses occurred more often in children who underwent cataract surgery at a younger age, had a better visual outcome, and were orthophoric at age 5 years. 12,13 The purpose of this study was to identify baseline factors, postoperative findings, and treatment compliance factors associated with both good visual acuity and stereopsis.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…[9][10][11] We have previously reported a positive stereopsis response to at least one stereopsis test at age 4.5 years in 25% of children in the IATS cohort. 12 We reported that positive stereopsis responses occurred more often in children who underwent cataract surgery at a younger age, had a better visual outcome, and were orthophoric at age 5 years. 12,13 The purpose of this study was to identify baseline factors, postoperative findings, and treatment compliance factors associated with both good visual acuity and stereopsis.…”
Section: Introductionmentioning
confidence: 84%
“…12 We reported that positive stereopsis responses occurred more often in children who underwent cataract surgery at a younger age, had a better visual outcome, and were orthophoric at age 5 years. 12,13 The purpose of this study was to identify baseline factors, postoperative findings, and treatment compliance factors associated with both good visual acuity and stereopsis. Our hope was that by identifying these factors that treatment protocols would be modified to allow a higher percentage of children to achieve nearly normal visual function after unilateral congenital cataract surgery.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Visual outcomes are often disappointing. Younger age at surgery is associated with better visual outcomes 5,6 . Unilateral cases have a worse visual prognosis in the affected eye than bilateral: at six years after surgery, a median visual acuity 0.48 in bilateral and 1.0 logMAR (affected eye) in unilateral cases has been reported 3 .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, compared with older children and adults, young children tend to have a more substantial inflammatory response to cataract surgery. 3,4 This inflammatory response, which is characterized by the presence of cells and flare in the anterior chamber, occurs when the blood-aqueous barrier is compromised.…”
Section: Introductionmentioning
confidence: 99%